2000
DOI: 10.1023/a:1008324131519
|View full text |Cite
|
Sign up to set email alerts
|

A phase I–II study of concomitant chemoradiotherapy with paclitaxel (one-hour infusion), 5-fluorouracil and hydroxyurea with granulocyte colony stimulating factor support for patients with poor prognosis head and neck cancer

Abstract: The recommended phase II dose of this regimen is 5-FU 600 mg/m2/day x 120 hours (days 1-5), hydroxyurea 500 mg p.o. b.i.d. x 11 doses (days 1-6), paclitaxel 100 mg/m2 over one hour on day 2, and radiotherapy 150 cGy b.i.d. days 2-6. Concomitant chemotherapy and re-irradiation was feasible on this protocol and resulted in long-term survival in patients without other curative intent options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…The TFGX regimen followed from our experience with TFHX (21,22). TFGX differs from TFHX in that gemcitabine was given instead of hydroxyurea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TFGX regimen followed from our experience with TFHX (21,22). TFGX differs from TFHX in that gemcitabine was given instead of hydroxyurea.…”
Section: Discussionmentioning
confidence: 99%
“…The FHX (10 -12) and TFHX (20,21) regimens were initially studied in phase I trials in which patients with recurrent or second primary head and neck cancer (some previously irradiated), metastatic disease, poor prognosis, and/or poor anticipated survival were eligible. Eligibility criteria were the same in the present phase I trial, in which concurrent gemcitabine replaces hydroxyurea in TFHX regimen (TFGX regimen).…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent phase I study used paclitaxel, on day 1, only administered over 1 hour. This was shown to be feasible with a recommended phase II dose of paclitaxel of 100 mg/m 2 [24]. Tolerability was better than with the cisplatin-containing regimen, and hematologic toxicity was markedly lower than with the 120-hour infusion schedule.…”
Section: C-fhx and T-fhx Regimensmentioning
confidence: 99%
“…The regimen showed substantial locoregional activity, with objective response rates of more than 90% in both previously untreated and previously treated patients. This work led to additional phase I studies that suggested a role for chemoradiotherapy in locally recurrent disease [21][22][23][24].…”
Section: -Fu Hydroxyurea and Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation